Literary values in the deep rivers - Collado Román, Humberto (2020)
Literary values ​​shape the minds and hearts of students, impacting some more than others, according to our sensitivity and habit in reading books. In this way we learn the feeling of the soul of men, through literature: "The reading, even fragmentary, of Homer, Shakespeare, Balzac, Dostoevsky and Martí, can teach us more about the human condition than the rest of our knowledge”. (Espinoza, 1992). Instead, for Max Scheler values ​​are learned in one way: emotional, psychological, logical and thoughtful. Being one of the characteristics of the values ​​the hierarchy (ethical and aesthetic), which graduates the values ​​conceived in a priori way: “Sensitive values: pleasant-unpleasant, enjoy-suffer. Vital values: health, old age, death. Spiritual values: aesthetic, legal, gnoseological, etc. Religious values: happiness, despair, love, among others; getting to discover hatred, love, the moral act”. (Cited by Morrero,  1913). As we see the values ​​are important in the life of the culture of society and of men. It is important to find the nexus between the cooperation between one and the other.